2012
DOI: 10.5296/ijl.v4i3.1899
|View full text |Cite
|
Sign up to set email alerts
|

Gender Patterns on Facebook: A Sociolinguistic Perspective

Abstract: The research aims at tracing differences and similarities among the way sexes use internet particularly social networking site, Facebook. The differences exist on multiple levels and research shows that even on internet one is not a human being rather a 'man' or a 'woman'. All these have been exhibited through language and the choices they make. The findings show that women are into facebook for maintaining existing relationships by being polite while men are more likely to go for new relations and all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…There is little attention paid to the issue of gender, handful researches are available which deal with the online linguistic practices of males and females. Eckert & McConnell-Ginnet believe that women use more standard language than men (Nazir, 2012). The women choose the more standard or advanced form of any language than men do.…”
Section: Gender and Linguistic Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little attention paid to the issue of gender, handful researches are available which deal with the online linguistic practices of males and females. Eckert & McConnell-Ginnet believe that women use more standard language than men (Nazir, 2012). The women choose the more standard or advanced form of any language than men do.…”
Section: Gender and Linguistic Practicesmentioning
confidence: 99%
“…Being a language of technology, commerce, education and business, English has become the source of communication on social media as it is more privileged than any other language. In recent years social networks have provided great space for researchers to look into linguistic patterns of male and female speakers of different languages especially the posts, comments and profiles on Facebook (Nazir, 2012). As it is a common thought that linguistic practices of men and women are different and males and females have different approaches towards language in a society.…”
Section: Introductionmentioning
confidence: 99%
“…Gender differences were also found in the purpose of using Facebook. Nazir (2012) indicated that women were using Facebook to maintain existing relationships, pass the time, and be entertained. On the other hand, men were more likely to go to Facebook to develop new relationships or meet new people.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Facebook is one of these social networking sites that allow individuals to construct a public or semi-public profile within a bounded system, share information, and create a personal background. Consequently, Facebook has opened the door for the scrutiny of gender differences in terms of language and profile picture, profile identity, language variation, privacy issue, groups, and topics both gender use (Nazir, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have been explored regarding the gender pattern in social media. Barirah Nazir [7] "Gender Patterns on Facebook: A Sociolinguistics Perspective" was done in Department of English, University of Sargodha Punjab, Pakistan. Her research was focusing on the differences and similarities tracing on genders using social network which shown that in maintaining the relationship by being polite was done by women while men love to find new relationship.…”
Section: Introductionmentioning
confidence: 99%